Maize pollen carry bacteria that suppress a fungal pathogen that enters through the male gamete fertilization route - Shrestha, Anuja; Limay-Rios, Victor; Brettingham, Dylan J. L.; Raizada, Manish N. (Frontiers in Plant Science, 2024)
In flowering plants, after being released from pollen grains, the male gametes use the style channel to migrate towards the ovary where they fertilize awaiting eggs. Environmental pathogens exploit the style passage, resulting in diseased progeny seed. The belief is that pollen also transmits pathogens into the style. By contrast, we hypothesized that pollen carries beneficial microbes that suppress environmental pathogens on the style passage. No prior studies have reported pollen-associated bacterial functions in any plant species. Here, bacteria were cultured from maize (corn) pollen encompassing wild ancestors and farmer-selected landraces from across the Americas, grown in a common field in Canada for one season. In total, 298 unique bacterial isolates were isolated, spanning 45 genera, 103 species, and 88 OTUs, dominated by Pantoea, Bacillus, Pseudomonas, Erwinia, and Microbacterium. Full-length 16S DNA-based taxonomic profiling showed that 78% of bacterial taxa from the major wild ancestor of maize (Parviglumis teosinte) were present in at least one cultivated landrace. The species names of the bacterial isolates were used to search the pathogen literature systematically; this preliminary evidence predicted that the vast majority of the pollen-associated bacteria analyzed are not maize pathogens. The pollen-associated bacteria were tested in vitro against a style-invading Fusarium pathogen shown to cause Gibberella ear rot (GER): 14 isolates inhibited this pathogen. Genome mining showed that all the anti-Fusarium bacterial species encode phzF, associated with biosynthesis of the natural fungicide, phenazine. To mimic the male gamete migration route, three pollen-associated bacterial strains were sprayed onto styles (silks), followed by Fusarium inoculation; these bacteria reduced GER symptoms and mycotoxin accumulation in progeny seed. Confocal microscopy was used to search for direct evidence that pollen-associated bacteria can defend living silks against Fusarium graminearum (Fg); bacterial strain AS541 (Kluyvera intermedia), isolated from pollen of ancestral Parviglumis, was observed to colonize the susceptible style/silk entry points of Fg (silk epidermis, trichomes, wounds). Furthermore, on style/silk tissue, AS541 colonized/aggregated on Fg hyphae, and was associated with Fg hyphal breaks. These results suggest that pollen has the potential to carry bacteria that can defend the style/silk passage against an environmental pathogen -- a novel observation.